Neural Correlates of Non-ordinary States of Consciousness in Pranayama Practitioners: The Role of Slow Nasal Breathing - Zaccaro, Andrea; Piarulli, Andrea; Melosini, Lorenza; Menicucci, Danilo; Gemignani, Angelo (Frontiers in Systems Neuroscience, 2022)
The modulatory effect of nasal respiration on integrative brain functions and hence consciousness has recently been unambiguously demonstrated. This effect is sustained by the olfactory epithelium mechanical sensitivity complemented by the existence of massive projections between the olfactory bulb and the prefrontal cortex. However, studies on slow nasal breathing in the context of contemplative practices, have sustained the fundamental role of respiratory vagal stimulation, with little attention to the contribution of the olfactory epithelium mechanical stimulation. This study aims at disentangling the effects of olfactory epithelium stimulation (proper of nasal breathing) from those related to respiratory vagal stimulation (common to slow nasal and mouth breathing). We investigated the psychophysiological (cardio-respiratory and electroencephalographic parameters), and phenomenological (Perceived State of Consciousness) after-effects of slow nasal breathing (Samavritti Pranayama - 2.5 breaths/min) in 12 experienced meditators. We compared the nasal breathing after-effects with those observed after a session of mouth breathing at the same respiratory rate, and with those related to a resting state condition. Slow nasal breathing induced 1) a slowing of EEG activities (delta-theta bands) in prefrontal regions, 2) a widespread increase of theta and high-beta connectivity complemented by an increase of phase-amplitude coupling between the two bands in prefrontal and posterior regions belonging to the Default Mode Network, 3) an increase of high-beta networks small-worldness. 4) a higher perception of being in a non-ordinary state of consciousness. The emerging scenario strongly suggests that the effects of slow nasal breathing, beyond the relative contribution of vagal stimulation, are mainly ascribable to olfactory epithelium stimulation. In conclusion, respiration, brain activity, and subjective experience are intermingled in a neurophysiological domain able to explain non-ordinary states of consciousness induced by slow breathing in the context of meditative practices.